Conversation Analysis on Turn-taking Strategies in Oprah Winfrey Show - Hendar (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this research is to identify the types of turn taking used by Oprah Winfrey, the host of The Oprah Winfrey Show. The method used in this research is descriptive qualitative method. In descriptive qualitative method, the data were systematically and accurately analysed based on the theory applied in the study. The main theory on types of turn taking strategies used in this study is taken from Sacks, Schegloff, and Jefferson (1974). The data obtained are classified into three types of turn taking strategies; taking the turn, holding the turn and yielding the turn, and each of which is divided into three or four subtypes or subcategories of turn taking strategies. The results of this research showed that of 35 data found in Oprah Winfrey Show, there were 26 (74,5%) data on yielding the turn, 6 (17%) data on taking the turn, and 3 (8,5%) data on holding the turn. The most dominant of subtypes of yielding is prompting. it is no wonder that Oprah as the host of The Oprah Winfrey Show dominantly asks, greets, invites, offers, questions or requests her guests in her Show as clearly seen at least in 3 episodes of her Show.